Analisis Postur Kerja Pada Operator Quality Control Menggunakan Metode RULA (Studi Kasus Pada PT. XYZ Cikarang Barat - Muhammad Hatta Mahmuda; Rana Ardila Rahma (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2024)
Work in the current industrial era, both on a small to large scale, almost always carries a risk of danger. One of them is an occupational disease caused by errors in posture when doing work. Illnesses caused by work posture errors usually do not have an immediate effect after finishing the job, but sometimes the impact often appears after quite a long time. Body posture is a determinant in assessing effectiveness at work. If the employee's posture is ergonomic then the results of the work will be good and the health of the workers is guaranteed. However, if the employee's posture is not ergonomic, then the results of the work are not necessarily good and can cause complaints on the body. In this study aims to analyze the performance posture of an employee in the quality control division. The method used is to use the nordic body map questionnaire and RULA calculations. The results obtained from the nordic body map questionnaire are that it can be seen which part of the body experiences pain, namely the upper body posture. While the results obtained from the RULA calculations were on the work of wiping components and checking data on the computer, the grand score obtained was 4, which means that it needs further investigation and if necessary repairs are made. Meanwhile, for the work of polishing components and measuring components, a grand score of 7 was obtained, which means that it needs to be investigated and repaired right away.